Peran Kepemimpinan Dalam Memperkuaat Komitmen Organisasi - Laoli, Masaati; Angel Dirawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the role of leadership in strengthening organizational commitment through a qualitative approach with case study methods. Leadership is a key factor in forming employee organizational commitment which ultimately affects organizational performance. This research examines the relationship between leadership style, organizational commitment, and employee performance. The findings indicate that effective leadership can create harmonious work communication between leaders and employees, thereby increasing employees' willingness to work, loyalty, and pride in the organization. Organizations that have leaders with good technical, human, and conceptual skills show higher levels of employee organizational commitment. Strong organizational commitment has a positive impact on improving performance, work motivation, productivity, reducing absenteeism, and decreasing employee turnover. Strategic planning combined with transformational leadership enables organizations to achieve goals more optimally through high employee involvement and loyalty.